Evaluation of Response Reduction Factor of Existing Masonry Infilled RC-Buildings in Pokhara - Pandit, Tekkan; Chaulagain, Hemchandra (Himalayan Journal of Applied Science and Engineering, 2020)
Most of the structural designer do not consider masonry infill walls during design process due to a lack of modeling guidelines in design standards and are treated as non-structural elements. In fact, the interaction effect between bounding frames and infill masonry is a complicated issue in nonlinearity of structures. The current seismic codes indirectly incorporate the nonlinear response of structure through linear elastic approach by considering the response reduction factor ‘R’ without comprising infill. In this context, this study evaluates the response reduction factor of existing engineered designed RC frame structures that are designed based on Indian standard codes. For this, three existing RC buildings were selected and performed non-linear pushover analysis. The structural response was examined in terms of natural period, base shear, strength, stiffness, ductility and response reduction factor. The results specify that the buildings with infill walls significantly influence on ‘R’ value of structures. Additionally, study shows that the variation of ‘R’ value mainly depends on the percentage of infill inclusion.